Mapping The Landscape of Performance on Budgetary Slack Research: Analysis Using VOSViewer - Desriani, Neny; Maheswari, Fidela Salsabilla; Mirza. BR, Aryan Danil; Saputra, M Rizky Rico; Handayani, Putri; Al-ghifari, Abidzar Septawandra (Economic Education and Entrepreneurship Journal, 2024)
This study aims to identify the development map of research related to performance on budgetary slack by using bibliometric analysis methods to assess bibliographic data, including the number of authors, number of journals, and keywords of articles. This study uses article publication data from 1981-2023 in research on the theme "Performance on Budgetary Slack". Data collection is done through the Publish or Perish (PoP) application using the source of Scopus indexed articles. This bibliometric analysis is a valuable resource for scholars, students, and practitioners interested in the dynamics of budgetary slack and its impact on organizational performance. It provides insight into the development of the field, highlights influential works, and provides guidance for further exploration of important aspects in management control system.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.134-144